THE INFLUENCE OF INFLUENCERS IN MARKETING OF SYARIAH BANKING PRODUCTS - Ai Reni Ratnasari; Dadi Wardiman; Akfah Zakiah J; Ahmad Nurkamali; Jalaluddin (Gunung Djati Conference Series, 2025)
This study aims to analyze the influence of influencers in marketing Islamic banking products. The research method used is a qualitative approach with data collection techniques through literature studies. Data analysis was carried out descriptively-analytical by reviewing literature related to digital marketing, the role of influencers, and the principles of Islamic banking. The results of the study indicate that influencers have a strategic role as a communication bridge between Islamic banking and the community, especially the younger generation, through authentic and educational content. Influencers also contribute to building customer trust by prioritizing the values ​​of honesty and blessings according to Islamic principles. The marketing strategy through influencers selected based on credibility and conformity with religious values ​​has proven effective in increasing loyalty and brand awareness. Internal support from the institution, including supervision by the Sharia Supervisory Board, is an important factor in the success of this strategy. Overall, the use of influencers as a digital marketing medium can strengthen the position of Islamic banking in the market and encourage sustainable growth.